2012
DOI: 10.1016/j.neuroimage.2012.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve impacts on inter-individual variability in resting-state cerebral metabolism in normal aging

Abstract: There is a great deal of heterogeneity in the impact of aging on cognition and cerebral functioning. One potential factor contributing to individual differences among the elders is the cognitive reserve, which designates the partial protection from the deleterious effects of aging that lifetime experience provides. Neuroimaging studies examining task-related activation in elderly people suggested that cognitive reserve takes the form of more efficient use of brain networks and/or greater ability to recruit alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 75 publications
(89 reference statements)
4
83
0
2
Order By: Relevance
“…Yet, additional analyses with vocabulary as proxy of verbal intelligence (Baddeley et al, 1993;Bastin et al, 2012) did not reveal any significant relationships (data not shown). Finally, we cannot exclude that the differences in data acquisition protocols between two centers have influenced our PET findings.…”
Section: Discussionmentioning
confidence: 88%
“…Yet, additional analyses with vocabulary as proxy of verbal intelligence (Baddeley et al, 1993;Bastin et al, 2012) did not reveal any significant relationships (data not shown). Finally, we cannot exclude that the differences in data acquisition protocols between two centers have influenced our PET findings.…”
Section: Discussionmentioning
confidence: 88%
“…This is important yet to highlight the relative contribution of education to cognitive and brain reserve as well as to provide a further understanding of the role of this factor in healthy brain aging. In a previous study, we failed to evidence positive relationships between a reserve proxy (combining verbal intelligence and education) and FDG-PET or resting state functional connectivity while inverse relationships were found (Bastin et al, 2012). We hypothesize that the selection of a 6 population of healthy elders based on strict criteria including amyloid imaging to exclude preclinical Alzheimer"s disease cases would allow highlighting positive relationships.…”
Section: Introductionmentioning
confidence: 76%
“…Thirty-nine right-handed healthy elders (mean age (±SD): 67.14 (±5.45), range 60-80; mean MMSE (±SD): 29.33 (±0.96), range 27-30; 24 women) were recruited after detailed clinical and neuropsychological examinations, part of which (25/39) were also included in Bastin et al (2012). Neuropsychological testing included memory, language, executive functions, visuo-spatial functioning and praxis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations